Evaluating the Impact of Pulmonary Artery Obstruction After Lung Transplant Surgery: A Systematic Review and Meta-analysis. Issue 4 (4th August 2020) - Kumar, Nicolas; Hussain, Nasir; Kumar, Julia; Essandoh, Michael K.; Bhatt, Amar M.; Awad, Hamdy; Perez, William J.; Whitson, Bryan A.; Ganapathi, Asvin M.; Mokadam, Nahush A.; Gorelik, Leonid; Turner, Katja; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Pulmonary artery obstruction is an uncommon but significant complication after lung transplantation. Although numerous reports have documented its occurrence, the hemodynamic parameters associated with its presentation and diagnostic considerations remain ill-defined. This systematic review summarizes evidence in the literature surrounding pulmonary artery obstruction after lung transplantation surgery. Methods: Databases were searched for all articles and abstracts reporting on pulmonary artery obstruction. Data collected included the number of patients studied, patient characteristics, incidences of pulmonary artery obstruction, and timing and imaging modality used for diagnosis. Results: Thirty-four full-text citations were included in this review. The point prevalence of pulmonary artery obstruction was 3.66%. The peak pulmonary artery velocity associated with obstruction was found to be 2.60 ± 0.58 m/s. The diameter of the obstructed pulmonary artery predictive of poor outcomes was noted to be 0.78 ± 0.40 cm. The majority of diagnoses were made in the late postoperative period using pulmonary angiogram and transesophageal echocardiography. Overall, 76% of patients (47 of 62) required emergent procedural reintervention, and 23% of patients (14 of 62) diagnosed with pulmonary artery obstruction died during their hospital stay. Conclusions: This systematic review underscores the importance of identifying pulmonary artery obstruction immediately after lung transplant surgery. The clinical implications of these results warrant the development of identification and management strategies for early detection of irregularities in pulmonary artery anastomosis in lung transplant patients.